The prevalence and severity of syndrome Z in severely obese male patients on the waiting list for bariatric surgery. A cross‑sectional study protocol - Perez, Eduardo A.; Junior, Wilson Rodrigues; Silva, Anderson Soares; Urbano, Jessica Julioti; Lottenberg, Carina; Brunetti, Ana Carolina Monteiro; Alves, Vera Lucia dos Santos; Oliveira, Patrícia Clemente; Peixoto, Roger André Oliveira; Oliveira, Ezequiel Fernandes; Nacif, Sergio Roberto; Santos, Israel Reis dos; et al. (Manual Therapy, Posturology & Rehabilitation Journal, 2016)
Introduction: The Syndrome Z (SyndZ) has been drawing scientific community’s attention on the past years. It is characterized by the interaction between obstructive sleep apnea (OSA) and Metabolic Syndrome (MetS). On its turn, MetS is knew for the association with various metabolic disturbances occurring simultaneously in the same patient, those of which include central obesity, systemic hypertension (SH), glucose intolerance or insulin resitance, low serum high-density lipoprotein cholesterol (HDL), and elevated serum triglycerides. OSA is a prevalent condition all over the world, and presents potential adverse health outcomes, with a particular impact in cardiovascular diseases. Therefore, OSA and MetS present important cardiovascular risk factors, that when superimposed can mean a higher cardiovascular morbi-mortality. This associated pathogenesis has not been completely elucidated. Objectives: A pilot study to determine the prevalence and severity of SyndZ in severely obese female patients on the waiting list for bariatric surgery. Methods/Design: This cross-sectional study will be conducted with severely obese female patients, on waiting list for bariatric surgery, from the Santa Casa de Misericordia de São Paulo Hospital, in the city of Sao Paulo (Brazil). Demographic, anthropometric and clinical data will be collected, as well as blood’s biochemical analysis. The patients will also undergo standard overnight polysomnography at the Sleep Laboratory of Nove de Julho University.